FACTORS AFFECTING PREVENTION PRACTICES OF DENGUE FEVER WITHIN THE COMMUNITIES IN ACEH PROVINCE, INDONESIA - Zubir (Malaysian Journal of Public Health Medicine, 2018)
Dengue fever is a mosquito-borne disease that occurs in tropical and sub-tropical areas of the world. A severe form of dengue fever, also called dengue haemorrhagic fever, can cause severe bleeding, a sudden drop in blood pressure (shock) and death. The incidence of dengue fever has grown dramatically around the world in recent decades. The purpose of this study was to determine factors affecting prevention practices for dengue fever within the community. A cross-sectional study was conducted in the the municipality of Banda Aceh and district of Aceh Besar, Aceh Province, Indonesia. The sample size was 203, and the study instrument was a questionnaire. The study results showed that female respondents, 71 (75,5%) seem to have practiced prevention of dengue fever more as compared to the males (58,7%) or 64 respondents. Respondents in early adulthood (75 people or 54.7%) practiced more dengue prevention than older respondents. Meanwhile, respondents with higher levels of education, 85 (87.6%) practiced more dengue prevention than respondents with a middle level of education (47.2%) or 50 respondents. Respondents with good knowledge about dengue fever 128 (74%) practiced more prevention of dengue fever than respondent with a poor knowledge (23.3%) or 7 respondents. Respondents who had a positive attitude to the prevention of dengue fever, 108 (85.7%) practiced much more prevention than respondents who had a negative attitude (33.3%) or 25 respondents. Factors most affecting prevention practices for dengue fever were knowledge, attitude, education level, age and gender. Health promotion related to prevention of dengue fever should be done more in the media, especially using televison.